PEMBELAJARAN KETERAMPILAN MENULIS PUISI DENGAN MENGGUNAKAN MEDIA GAMBAR BERBASIS ANDROID PADA SISWA SMAN 1 BABAT - Sutam Fanny Rahimansyah; Iib Marzuqi; Nisaul Barokati Selirowangi (Pendidikan Bahasa dan Sastra Indonesia, 2023)
Education plays an important role in the development of students' skills and knowledge. One of the factors that can support the success of learning is the selection of the appropriate learning media. Along with technological advancements, Android-based learning media has become increasingly popular due to its flexibility and easy access, particularly in visual-based learning. This study aims to examine the effectiveness of using Android-based image media in teaching poetry writing skills at SMA Negeri 1 Babat. The research employs a quantitative approach, collecting data through observations of student and teacher activities, poetry writing tests, and student responses to the applied learning. The results show that the use of Android-based image media successfully increased student participation, with student activity reaching 88.3%, and teacher activity achieving 94%. Students' learning mastery also improved, with a percentage of 81.4%. Student responses to this learning reached 78%, indicating a positive reception of the media used. Based on these results, it can be concluded that Android-based image media is effective in enhancing poetry writing skills and can serve as an innovative alternative in Indonesian language learning.